2020
DOI: 10.3389/fpls.2020.565339
|View full text |Cite
|
Sign up to set email alerts
|

Root Adaptation via Common Genetic Factors Conditioning Tolerance to Multiple Stresses for Crops Cultivated on Acidic Tropical Soils

Abstract: Crop tolerance to multiple abiotic stresses has long been pursued as a Holy Grail in plant breeding efforts that target crop adaptation to tropical soils. On tropical, acidic soils, aluminum (Al) toxicity, low phosphorus (P) availability and drought stress are the major limitations to yield stability. Molecular breeding based on a small suite of pleiotropic genes, particularly those with moderate to major phenotypic effects, could help circumvent the need for complex breeding designs and large population sizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 277 publications
(376 reference statements)
0
20
0
Order By: Relevance
“…One of the biggest problems of modern agronomy and a constraint for world agriculture is the progressive acidification of arable lands, caused by industrial pollution and overuse of ammonia- and amide-containing fertilizers. It is estimated that up to 50% of arable lands worldwide are acidic, with a pH below 5.5 ( Von Uexküll and Mutert, 1995 ; Singh et al, 2017 ; Barros et al, 2020 ). The majority of crops growing in acidic soils show significant yield losses - up to 80%, depending on the species ( Sade et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the biggest problems of modern agronomy and a constraint for world agriculture is the progressive acidification of arable lands, caused by industrial pollution and overuse of ammonia- and amide-containing fertilizers. It is estimated that up to 50% of arable lands worldwide are acidic, with a pH below 5.5 ( Von Uexküll and Mutert, 1995 ; Singh et al, 2017 ; Barros et al, 2020 ). The majority of crops growing in acidic soils show significant yield losses - up to 80%, depending on the species ( Sade et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…P use eficiency in plants can be achieved by mechanisms underlying both P acquisition and P internal utilization efficiency (Parentoni and Souza-Junior, 2008). P bioavailability is generally greatest in the topsoil and foraging can be improved through several mechanisms, such as production of axial roots, shallower axial root growth angles, greater lateral root density, reduced root metabolic cost, which vary among species and genotypes (Barros et al, 2020;Wen et al, 2019;Magalhães et al, 2017).…”
Section: Sorghum Root System Phenotypingmentioning
confidence: 99%
“…Many compounds in exudates have been shown to contribute to shaping the microbial community by recruiting microbes, such as fungi [ 10 ] and bacteria with different metabolic capacities [ 11 13 ]. Knowledge of how exudates interact with specific beneficial microbes in the rhizosphere may eventually be used to enhance crop production and crop tolerance to stress [ 14 16 ]. Although to date few studies have focused on modulating exudation to improve crop yield, recent reports showed that regulation of the AtALMT1 aluminum-activated root malate transporter, responsible for malate exudation, affects crop tolerance to aluminum toxicity, low phosphorus availability, and drought stress [ 14 ].…”
Section: Introductionmentioning
confidence: 99%